Pharmacology of Antiretrovirals in the Female Genital Tract for HIV Prevention. (14th June 2018) - Nicol, Melanie R.; Corbino, Joseph A.; Cottrell, Mackenzie L.
Abstract: Preexposure prophylaxis (PrEP) is a powerful tool that, as part of a comprehensive prevention package, has potential to significantly impact the HIV epidemic. PrEP effectiveness is believed to be dependent on the exposure and efficacy of antiretrovirals at the site of HIV transmission. Clinical trial results as well as modeling and simulation indicate the threshold of adherence required for PrEP efficacy of emtricitabine/tenofovir disoproxil fumarate may differ between sites of HIV transmission with less forgiveness for missed doses in women exposed through genital tissue compared to people exposed through colorectal tissue. This suggests a role for local and host factors to influence mucosal pharmacology. Here we review the mucosal pharmacology of antiretrovirals in the female genital tract and explore potential determinants of PrEP efficacy. Host factors such as inflammation, coinfections, hormonal status, and the vaginal microbiome will be explored as well as the role of drug‐metabolizing enzymes and transporters in regulating local drug exposure. The use of preclinical and early clinical models to predict clinical effectiveness is also discussed.